From branding to authority: UNESCO heritage and the institutionalisation of breakfast culture in multi-ethnic Malaysia - Liu, Ziyuan; Hussin, Hanafi; Subramaniam, Thirunaukarasu (Research Journal in Advanced Humanities, 2026)
The paper discusses the redefining role of the political and diplomatic agency of food in international cultural governance with reference to the 2024 UNESCO inscription of “Breakfast culture in Malaysia: dining experience in a multi-ethnic society”. Going beyond the conventional imagination of gastronomy as soft power, the article posits that UNESCO recognition shifts routine breakfast practices into an institutionalised cultural power. By conducting a qualitative discourse analysis of UNESCO nomination files, evaluation reports, and Malaysian policy statements, the research shows how banal practices such as eating nasi lemak or drinking teh tarik are formalised, legitimised, and elevated within a global heritage regime. The results suggest that such a breakfast culture is not simply a creation of tourism branding or gastronomic appeal, but rather a form of institutional identity grounded in procedural validity. The incorporation of everyday gastronomy into an international governance system will allow Malaysia to convey a message of multicultural coexistence, grounded in credibility and recognition, rather than merely serving as a promotional spectacle. This act is a big step towards cultural diplomacy, in which ordinary social relations are elevated to a stable diplomatic value through institutional certification.